Pengaruh Kredit Bermasalah, Perputaran Kas, Efisiensi Operasional, Dana Pihak Ketiga, dan Likuiditas terhadap Profitabilitas pada Perusahaan Perbankan - Danny Lintang; Kenny Ardillah (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This study aims to determine the effect of non-performing loans, cash turnover, operational efficiency, third party funds, and liquidity on profitability (ROA and ROE). Research Methodology: The method used is panel data regression with a Random Effects model approach. Results: Non-performing loans have no effect on ROA and ROE. Cash turnover has no effect on ROA. Operational efficiency affects ROA and ROE. Third party funds affect ROA but have no effect on ROE. Liquidity affects ROA but has no effect on ROE. Limitations: This study uses data from banking companies with selection based on certain criteria and does not reflect the entire financial industry in general. Contribution: Bank’s management can maintain non-performing loans, cash flow, operational efficiency, third party funds, liquidity, and profitability carefully and in accordance with the latest regulations issued by Bank Indonesia, the Ministry of Finance, and the Financial Services Authority.